Saving for retirement intention, context, and behavior - Clark, Gordon L. 1950-; Strauss, Kendra; Knox-Hayes, Janelle 1983- (Oxford University Press, 2012)
As individuals assume greater responsibility for retirement saving, the book analyses how people save and make financial decisions, taking into account the behavioural revolution and the effect of society and context
Includes bibliographical references and index
Keywords: Retirement income / Planning; Finance, Personal